The Banff : urban concept plan (Parks Canada, 1979)
This Plan for the town of Banff briefly summarizes decisions needs to guide the growth and mangement of Banff over the next several years. These decisions reflect the national and regional significance of the town, traditional and changing patterns of use, the National Parks Act and Policies.